2014
DOI: 10.1111/acer.12499
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ghrelin Antagonists [DLys3]‐GHRP‐6 or JMV2959 on Ethanol, Water, and Food Intake in C57BL/6J Mice

Abstract: Background Alcohol use and abuse patterns have created a need for novel treatment models. Current research has turned its focus on reward pathways associated with intrinsic necessities, such as feeding. Theories suggest that drugs of abuse seize control of natural reward pathways and disregulate normal function, leading to chronic addiction. One such pathway involving the hunger stimulating peptide, ghrelin, is the focus of our study. Methods Male C57BL/6 mice were randomly assigned to groups and treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 34 publications
(52 reference statements)
7
29
0
Order By: Relevance
“…In experiment 2, sterile water was used as the vehicle. All solutions were prepared fresh daily and different doses of drugs were used in mice and rats based on previously published experiments (Jerlhag et al, 2009; Kaur and Ryabinin, 2010; Gomez and Ryabinin, 2014). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiment 2, sterile water was used as the vehicle. All solutions were prepared fresh daily and different doses of drugs were used in mice and rats based on previously published experiments (Jerlhag et al, 2009; Kaur and Ryabinin, 2010; Gomez and Ryabinin, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…For each testing period, a three-way repeated measures ANOVA was used with vapor and drug as between-subjects factors and day as the within-subjects factor. Planned comparisons assessed the drug and vapor effects on day 1, as previous work determined this day to show the most robust effects (Gomez and Ryabinin, 2014). To determine any drug differences on day 1, a one-way ANOVA was used with post-hoc LSD.…”
Section: Methodsmentioning
confidence: 99%
“…In consistent with that, a recent study showed that [D-Lys3]-GHRP-6 did not decrease stress-induced caloric intake, but paradoxically increased the intake of HFD (343). Moreover, the infusion of [D-Lys3]-GHRP-6 in a rat model did not have a significant impact on food intake and appetite (342).…”
Section: Discussionsupporting
confidence: 78%
“…In consistent with that, more recent studies did not find a significant impact of the infusion of ghrelin antagonist [D-Lys3]-GHRP-6 on food intake and appetite in a rat model (342).…”
Section: Infusion Of [D-lys3supporting
confidence: 81%
See 1 more Smart Citation